THE EFFECTIVENESS OF MEDICATION THERAPY MANAGEMENT PROGRAMS TO OPTIMIZE PATIENT OUTCOMES - Sarah bhni Al haili,Abdullah Meshari Al- Mutairi,Tareq Abdulhafiz Abdulghafur Mohammed,Fatimah Mohammed Ahmed Alnami, Faleh Obaidallah Alreseheedi , ‎Mabruk Musallam Eid Alazmi , Abdalmjeed Awad ALazmi , ,; Lila Farhan Alatawi, Ammar Nuwahy Safir Alsahli, Mohammed Obaid Mohammed Aldawsari , Riyadh Ibrahim M Alshobaki ,,; Ahmad Noman Alsaleh, Mohanad Jamal Qadi, Alhnouf Adel Saad Alkhayat, Essam mohsen Mousa khormi، Ali Saeed A Alqahtani., (Chelonian Research Foundation, 2022)
Medication treatment management (MTM) services are a technique that may successfully enhance patients' circumstances, but the effectiveness of economic and humanistic results is still uncertain. This study aims to assess the many advantages of Medication Therapy Management (MTM) services by analyzing economic, clinical, and humanistic results using a systematic review and meta-analysis. A comprehensive review and meta-analysis was performed by accessing PubMed, EMBASE, the Cochrane Library, and ClinicalTrial.gov from their establishment until April 2022. Two reviewers independently screened the records, extracted the data, and assessed the quality of research. Our systematic review and meta-analysis revealed that MTM services significantly enhanced patients' clinical conditions. However, the effectiveness of economic and humanistic outcomes varied considerably, indicating the need for further studies to establish more robust evidence due to potential publication bias and heterogeneity in the results. Keywords: Medication treatment management (MTM), review, patients' clinical conditions, patient.